El calvario de los brigadistas húngaros - Anderle, Ádám (Acta Hispanica, 2013)
The elite of the Hungarian volunteers of the Spanish Civil War became victim of the Communist terror after World War II (1949-1950). The main role was played by the brigadist, László Rajk, who, before the trial, was the secretary of the Hungarian Communist Party, Minister of the Interior, and then Minister of Foreign Affairs. He was charged with spying for the “imperialists” and Tito as well as with high treason and anti-Semitism. In the show trial of “Rajk and his associates” 155 people were charged and convicted, 15 of them, including Rajk, were condemned to death. In the indictment Rajk was condemned for his activity during the Spanish Civil War: he was accused of being a fascist, and then an imperialist agent, as well as a “Trockyist”, just like the twenty other Hungarian Brigadists. The background of the trial has been thoroughly analysed in Hungarian historiography, but the accusation connected to the Spanish period has not been examined or criticized. The present study, based on new sources, such as the reports of the Hungarian Communist Secret Service, the papers of the KGB Archives in Moscow, and the Comintern, raises the issue emphasizing the negative role of Ernő Gerő (“Pedro”), who was the representative of the Comintern and the PCIA (People’s Commissariat for Internal Affairs), in the process.